Talins, hopes and promises - Mohamed S. Attia Gaballah; Mahmoud Youns; Zeinab A. Hassan (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2017)
Talins were the firstly identifi ed cytoplasmic protein partners of integrins. Vertebrates have two talin genes, TLN1 and TLN2, which encode Talin-1 and Talin-2, respectively. Talin-1 is essential for cell adhesion and motility and is the primary talin component of focal adhesions. Many studies have demonstrated, involvement of talins in different mechanisms inside many body cells, induction of some diseases. Moreover, recent and ongoing research indicates the diagnostic and prognostic roles of talins in various clinical settings especially in critically ill patients. Additionally, talins may be a good target for treatment of certain types of diseases. Talins levels are altered in various physiological and pathological conditions indicating its importance and possible use as a biomarker or a tool for diagnosis or treatment. However, further research using talins in various clinical settings will prove its cost-effectiveness and clinical usefulness.